PENETAPAN KADAR ASAM ASETILSALISILAT DAN ASAM ASCORBAT DENGAN MENGGUNAKAN METODE TITRASI ACIDIMETRI- ALKALIMETRI - Rahmadani Rahmadani; Vinda Amelia; Khusnul Khatimah Septiany; Winanda Amelia Bahari; Nur Afnan Aulia Anwar; Reva Ananda; Hendry Pratiwi; Putri Amara Bintang; Nurul Pebrianti; Firda Firda (Kampus Akademik Publiser, 2025)
Acidimetry is a titration using an acidic standard solution to determine the base. The acids usually used are HCl, vinegar, oxalic acid, boric acid. While alkalimetry is the opposite of acidimetry, namely titration using a standard solution of base to determine the acid. This study aims to analyze the levels of acetyl salicylic acid and ascorbic acid. The method used is a laboratory experiment carried out with several stages of preparation of reagent solutions, preparation of indicators and acid-alkalimetric titration on samples. The results of the determination of the content analysis of acetosal content obtained an average of 57.3115 mg, and ascorbic acid (vitamin C) levels with the sample “Vit C 50 mg” levels 166.6955 mg.